Analisis Kritis Prospek Pemerintahan Efektif Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Ogan Komering Ilir - Pebriadi, Elpis; Putra , Raniasa (Syntax Corporation, 2025)
This study analyzes the prospects for effective governance at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Ogan Komering Ilir (OKI) Regency using qualitative case study methods and document analysis. DPMPTSP demonstrates remarkable procedural effectiveness, with performance targets achieving more than 650% for licensing services and 438% for investment realization by 2024, as well as consistently achieving a Public Satisfaction Index (IKM) of